Design & economic analysis of a solar powered water pumping system for crop irrigation - Joynal, Jafrin Binte; Raka, Nuzhat Tabassum; Mithu, Hosaifa Mohon (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.